2014
DOI: 10.1002/pits.21762
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Educational Outcomes and Psychological Well-Being in Adolescents Using Time Attitude Profiles

Abstract: Using cluster analysis of Adolescent Time Attitude Scale (ATAS) scores in a sample of 300 adolescents (M age = 16 years; SD = 1.25; 60% male; 41% European American; 25.3% Asian American; 11% African American; 10.3% Latino), the authors identified five time attitude profiles based on positive and negative attitudes toward the past, present, and future. Four of the profiles identified in the present study were conceptually similar to profiles that emerged in a study in a German sample. Adolescents with profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
117
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 38 publications
12
117
1
Order By: Relevance
“…profiles of time attitude scores that have shown relationships with academic achievement in adolescents (Andretta, Worrell, & Mello, 2014), and to a study with college students that reported a positive association between the ZTPI-future subscale and self-reported hours studying per week . Further, we showed associations with social and emotional self-efficacies.…”
Section: Discussionmentioning
confidence: 96%
“…profiles of time attitude scores that have shown relationships with academic achievement in adolescents (Andretta, Worrell, & Mello, 2014), and to a study with college students that reported a positive association between the ZTPI-future subscale and self-reported hours studying per week . Further, we showed associations with social and emotional self-efficacies.…”
Section: Discussionmentioning
confidence: 96%
“…Most of the studies with adolescent samples (i.e., Alansari et al, 2013;Andretta et al, 2013Andretta et al, , 2014Buhl & Linder, 2009) have used the time attitude (TA) subscales of the Adolescent Time Inventory (ATI; Mello & Worrell, 2007), another multidimensional instrument. These groups of researchers classified adolescents into positive (e.g., Positives, Optimists, Balanced, and Ambivalents) and negative profiles (e.g.…”
Section: Temporal Profilesmentioning
confidence: 99%
“…In addition to the correlational findings, as reported in the Introduction, recent person-centred analyses have also demonstrated substantial associations between time attitude and time perspective profiles and indicators of well being (Alansari et al, 2013;Andretta et al, 2014;Cole et al, 2017;McKay et al, 2016). Importantly, in a longitudinal study, Wells, Morgan, Worrell, Sumnall, and McKay (2016) showed that adolescents who started and remained in positive profiles were less likely to use alcohol and had healthier attitudes towards alcohol, whereas those who transitioned to negative profiles reported more unhealthy drinking behaviors.…”
Section: Discussionmentioning
confidence: 79%
“…Several profiles have been found, including Positives, Optimists, Balanced, Ambivalents, Negatives, and Pessimists. Importantly, individuals with different profiles differ meaningfully on outcomes, with more positive profiles associated with more adaptive outcomes, including life satisfaction, mental health, and academic success (Alansari et al, 2013;Andretta et al, 2014;Buhl & Lindner, 2009;Cole et al, 2017;McKay, Percy, Cole, Worrell, & Andretta, 2016;Prow, Worrell, Andretta, & Mello, 2016. These differences across profiles have been found in Germany, New Zealand, the UK, and the US.…”
Section: The Adolescent and Adult Time Inventory-time Attitude Scalesmentioning
confidence: 99%
See 1 more Smart Citation